Strategi Guru Pendidikan Agama Islam dalam Menanggulangi Tindakan Bullying Siswa - Syaiful Fuad; Sumarwati Sumarwati; Asma Naily Fauziyah; Zaini Tamin AR (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2021)
This research stems from the author's observations as a teacher at SMPN 2 Waru Sidoarjo, who often finds bullying by students. From these activities, the authors conducted a study that aims to find out what forms of bullying acts and strategies for Islamic Religious Education Teacher teachers in dealing with bullying behavior in students. The type of research used is descriptive qualitative research with a case study approach. This study found that the forms of bullying carried out by children such as pushing their friends' bodies, mocking, insulting their families, kicking, hitting, pushing their heads, and so on. There are three strategies used by Islamic Religious Education teachers in dealing with bullying behavior: first, the lecture strategy, providing direction and advice to students. Second, the punishment strategy is given by memorizing short verses, cleaning the classroom, and other punishments that are negotiated with the school and parents. The author recommends several things: first, guidance to students must be carried out continuously, whether at school, at home or in the community. Second, communicate intensely with the guardians of students. This activity is carried out to inform parents of student activities properly. Third, teachers must prioritize exemplary. Because learning in class will be meaningful if it is supported by good examples. Fourth, schools must make standard rules that become laws to combat student bullying.